Analysis of the clinical antibacterial and antituberculosis pipeline. Issue 2 (February 2019) - Theuretzbacher, Ursula; Gottwalt, Simon; Beyer, Peter; Butler, Mark; Czaplewski, Lloyd; Lienhardt, Christian; Moja, Lorenzo; Paul, Mical; Paulin, Sarah; Rex, John H; Silver, Lynn L; Spigelman, Melvin; et al.
Summary: This analysis of the global clinical antibacterial pipeline was done in support of the Global Action Plan on Antimicrobial Resistance. The study analysed to what extent antibacterial and antimycobacterial drugs for systemic human use as well as oral non-systemic antibacterial drugs for Clostridium difficile infections were active against pathogens included in the WHO priority pathogen list and their innovativeness measured by their absence of cross-resistance (new class, target, mode of action). As of July 1, 2018, 30 new chemical entity (NCE) antibacterial drugs, ten biologics, ten NCEs against Mycobacterium tuberculosis, and four NCEs against C difficile were identified. Of the 30 NCEs, 11 are expected to have some activity against at least one critical priority pathogen expressing carbapenem resistance. The clinical pipeline is dominated by derivatives of established classes and most development candidates display limited innovation. New antibacterial drugs without pre-existing cross-resistance are under-represented and are urgently needed, especially for geographical regions with high resistance rates among Gram-negative bacteria and M tuberculosis .